2022
DOI: 10.1155/2022/3312589
|View full text |Cite
|
Sign up to set email alerts
|

Far-Contralateral Oblique (FCO) Sacroiliac Joint Injection: Description of a Novel Technique

Abstract: Sacroiliac (SI) joint arthropathy is the primary pain generator in approximately 15–25% of patients with axial low back pain and traditionally diagnosed with >50% pain reduction following an intra-articular injection localized to the inferior 1/3 of the SI joint. The conventional technique for accessing the SI joint encompasses a posterior approach with fluoroscopic guidance at 10–20⁰ contralateral oblique angulation, and minor adjustments to this approach have been implemented with varying degrees of succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“… 14 Another study by Lee et al proposes the use of an alternative far-contralateral oblique approach for sacroiliac joint injection with lateral fluoroscopic imaging to confirm injection location. 15 Their study concluded that their proposed technique can be utilized to determine candidacy for SIJ fusion. Our study builds on these two studies by demonstrating the efficacy of an additional lateral view during SIJ injection.…”
Section: Discussionmentioning
confidence: 96%
“… 14 Another study by Lee et al proposes the use of an alternative far-contralateral oblique approach for sacroiliac joint injection with lateral fluoroscopic imaging to confirm injection location. 15 Their study concluded that their proposed technique can be utilized to determine candidacy for SIJ fusion. Our study builds on these two studies by demonstrating the efficacy of an additional lateral view during SIJ injection.…”
Section: Discussionmentioning
confidence: 96%